2018
DOI: 10.1101/440461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biofilm/Persister/Stationary Phase Bacteria Cause More Severe Disease Than Log Phase Bacteria – I BiofilmBorrelia burgdorferiNot Only Display More Tolerance to Lyme Antibiotics But Also Cause More Severe Pathology In a Mouse Arthritis Model: Implications for Understanding Persistence, PTLDS and Treatment Failure

Abstract: 24Lyme disease, caused by Borrelia burgdorferi, is the most common tick-borne illness in US and Europe. While 25 most patients can be cured with a 2-4 week antibiotic therapy, about 10%-20% patients continue to suffer 26 persistent symptoms of fatigue, pain or joint and muscle aches, and neurocognitive despite the treatment, a 27 condition called post-treatment Lyme disease syndrome (PTLDS). The cause for PTLDS is unclear but one 28 possibility is persistent infection with B. burgdorferi. B. burgdorferi is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Our results indicate that disseminated spirochetes of two different B. burgdorferi strains can persist in mice at 12 and 18 months following antimicrobial treatment. Noncultivable spirochetes persisted in mice (105), dogs (29), and nonhuman primates (54) inoculated with alternate strains of B. burgdorferi, so we have confirmed that persistence is not unique to N40.…”
Section: Discussionsupporting
confidence: 56%
“…Our results indicate that disseminated spirochetes of two different B. burgdorferi strains can persist in mice at 12 and 18 months following antimicrobial treatment. Noncultivable spirochetes persisted in mice (105), dogs (29), and nonhuman primates (54) inoculated with alternate strains of B. burgdorferi, so we have confirmed that persistence is not unique to N40.…”
Section: Discussionsupporting
confidence: 56%
“…Unfortunately, these researchers did not evaluate DDS combinations against attached B. burgdorferi biofilm, the most antibiotic resistant form in vitro [24,30] and a dominant form in a human autopsy study from a Lyme disease patient [31]. Furthermore, a recent mouse model study [42] showed that the biofilm like microcolony and stationary phase planktonic forms (free cells) caused more severe Lyme arthritis with an earlier onset of inflammation and joint swelling than the log phase spirochetes. Therefore, addressing biofilm forms is vital, and for that reason in this study, we added several assays to evaluate dapsone alone and in combination on B. burgdorferi biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo animal studies with immunocompetent mice, dog, and non-human primate models have identified a surviving, but not cultivatable form of B. burgdorferi that can withstand antibiotic treatment [16][17][18][19][20]. Recent studies on rhesus macaques and mice confirmed these observations by demonstrating a metabolically active, persistent B. burgdorferi post-treatment in antibiotic-treated animals [20][21][22][23][24]. There are also human studies providing clinical evidence that a chronic form of Lyme disease could be caused by a persistent spirochetal infection, which could explain the lingering symptoms [25][26][27][28].…”
Section: Introductionmentioning
confidence: 96%